Creative House Strategy For Increasing The Creativity of Micro, Small and Medium Enterprises (Umkm) Pappandangan Village Polman District - Chuduriah Sahabuddin; Ayu Rahayu; Sukmawati Sukmawati; Abdul Malik (International Journal Of Community Service, 2024)
The process of building the Village Creative House will have a new icon in increasing visitors and the economy of the local community. The function of the Village Creative House is as a place for training, mentoring, a place for production, a place for marketing the community's creative products and a place for the incubation process for creative products in Pappandangan village. This activity involved human resources from the Youth, Sports and Tourism Department of Polewali Mandar Regency, lecturers and students from Al Asyariah Mandar University as well as residents of Pappadangan village. The sub-activities in making Creative Houses are: village creative house building design, interior creation, wall decoration design, production training place layout, training place layout, marketing place creation layout. Apart from that, assistance is also provided to the community, namely: assistance to village art studios, assistance in processing typical village foods, assistance in processing Gadum plants (Dioscorea hispida) into chips and flour.